Impact of Clostridioides difficile Therapy on Nosocomial Acquisition of Vancomycin-Resistant Enterococci - Carlos L. Correa-Martínez; Niklas C. J. Hagemeier; Neele J. Froböse; Stefanie Kampmeier (MDPI AG, 2021)
Vancomycin is frequently used for the treatment of C. difficile infections (CDI). There are concerns that this might increase the risk of selecting vancomycin resistant enterococci (VRE). Here, we evaluated whether there is an increased risk of VRE acquisition following vancomycin for CDI specific treatment. Patients with CDI, metronidazole, or oral vancomycin treatment and without preexisting VRE were monitored for VRE acquisition. VRE isolates from patients with acquired and preexisting colonization were collected and subjected to whole genome sequencing. In total, 281 patients (median age 56 years, 54% of the male sex) presented with toxin positive C. difficile. Of them, 170 patients met the inclusion criteria, comprising 37 patients treated with metronidazole and 133 treated with oral vancomycin. In total, 14 patients meeting the inclusion criteria acquired VRE (vancomycin: n = 11; metronidazole: n = 3). Statistical analysis revealed no significant differences between both VRE acquisition rates. Genetic comparison of detected VRE isolates resulted in eight clusters of closely related genotypes comprising acquired and preexisting strains. Our results suggest that vancomycin and metronidazole likewise increase the risk of VRE acquisition. Genetic comparison indicates that VRE acquisition is a result of both antibiotic selection and pathogen transmission.